Emerging smart design of electrodes for micro‐supercapacitors: A review. Issue 3 (11th February 2022) - Qiu, Jiajia; Zhao, Huaping; Lei, Yong
Abstract: Owing to high power density and long cycle life, micro‐supercapacitors (MSCs) are regarded as a prevalent energy storage unit for miniaturized electronics in modern life. A major bottleneck is achieving enhanced energy density without sacrificing both power density and cycle life. To this end, designing electrodes in a "smart" way has emerged as an effective strategy to achieve a trade‐off between the energy and power densities of MSCs. In the past few years, considerable research efforts have been devoted to exploring new electrode materials for high capacitance, but designing clever configurations for electrodes has rarely been investigated from a structural point of view, which is also important for MSCs within a limited footprint area, in particular. This review article categorizes and arranges these "smart" design strategies of electrodes into three design concepts: layer‐by‐layer, scaffold‐assisted and rolling origami. The corresponding strengths and challenges are comprehensively summarized, and the potential solutions to resolve these challenges are pointed out. Finally, the smart design principle of the electrodes of MSCs and key perspectives for future research in this field are outlined. Abstract : Configuration of electrodes is important to achieve the trade‐off between the energy and power densities of micro‐supercapacitors (MSCs). An overview of the emerged "smart" design strategies of electrodes is presented for constructing MSCs with high areal energy storage and transportation performance by highlighting these strategies, outlining the challenges, put forward the corresponding potential solutions and perspective for next‐generation MSCs.